Perempuan dan Kekerasan pada Masa Orde Baru - Fatimah, Siti (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2007)
Many studies about women history, especially which of related to violence issues toward them, are strongly related to the issues of human rights and democratization. Along Indonesian history, the New Order era is assumed as the era that had high frequency of violence toward human rights, especially for women. The crucial issue of struggling for human rights and democratization is one of the issues related to social equity. This article tries to analyze some issues about women and violence during the New Order Era, especially that of related to the state policy of women in Indonesia, the violence opportunity of women, and the violence peak of women in the tragedy of Mei 1998. Kata Kunci: Perempuan, Kekerasan, Hak Asasi Manusia, Keadilan, Demokratisasi